Do subjective memory complaints predict falls, fractures and healthcare utilization? A two‐year prospective study based on a cohort of older women recruited from primary care. (18th July 2016) - Al‐Sari, Usama A.; Tobias, Jon H.; Archer, Hilary; Clark, Emma M.
Abstract : Objective: A proportion of older individuals report subjective memory complaints (SMCs), which can predict the development of cognitive impairment and dementia. Previous studies based on secondary care suggest that SMC is also associated with other adverse health consequences, including falls, fractures and increased healthcare utilization. In this study, we aimed to establish whether similar findings are observed in the wider population. Methods: Prospective analysis of the Cohort for Skeletal Health in Bristol and Avon, a population‐based cohort recruited from primary care, was carried out. Data were collected by self‐completion questionnaire at baseline and 2 years. SMC was assessed at baseline. Fractures, measures of falls, mobility and healthcare utilization were assessed 2 years later. A random 5% subsample of data was validated against electronic general practitioner records. Logistic regression was used to identify independent associations, following adjustment for a range of confounders assessed at baseline. Results: Data were available on 3184 women. Three hundred and fifty participants (11.0%) reported SMC. They were older (73.3 ± 4.5 vs 72.0 ± 4.2 years) and less mobile compared with those not reporting SMC. SMCs at baseline were associated with an increased risk of upper limb fractures over the following 2 years (OR 1.72, 95% CI 1.02–2.90). SMCs were also associated with an increased risk of falls (OR 1.83, 95% CI 1.41–2.38) and increased healthcare utilization (OR for hospital appointments 2.20, 95% CI 1.26–3.86). No association was observed with bone mineral density at any site. Conclusions: Subjective memory complaints are important markers of adverse health outcomes and should prompt interventions to reduce fractures such as physiotherapy‐led fall reduction programmes. Copyright © 2016 John Wiley & Sons, Ltd.